2004
DOI: 10.1055/s-2004-832349
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous, Multiple Meningiomas

Abstract: We suggest that surgery is suitable for the treatment of multiple meningiomas with the following characteristics: symptomatic meningioma, asymptomatic meningioma greater than 3 cm in size and surgically accessible, and asymptomatic expanding tumor. In patients with multiple tumors, each tumor must be treated as an individual entity. The mere presence of multiple tumors does not justify their removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Sixteen patients revealed further cranial nerve deficits, including Cranial Nerves III (n ϭ 4), IV (n ϭ 4), V (n ϭ 2), VI (n ϭ 2), and VIII (n ϭ 2), and unspecified diplopia (n ϭ 6) ( Table 2). Five patients harbored multiple meningiomas in terms of a meningiomatosis (30), and three patients had bilateral SOMs (Fig. 4).…”
Section: Clinical Datamentioning
confidence: 98%
“…Sixteen patients revealed further cranial nerve deficits, including Cranial Nerves III (n ϭ 4), IV (n ϭ 4), V (n ϭ 2), VI (n ϭ 2), and VIII (n ϭ 2), and unspecified diplopia (n ϭ 6) ( Table 2). Five patients harbored multiple meningiomas in terms of a meningiomatosis (30), and three patients had bilateral SOMs (Fig. 4).…”
Section: Clinical Datamentioning
confidence: 98%
“…Every tumor should be approached on a case by case basis, and just the presence of multiple tumors does not justify their removal. 11,12 Since it is well documented that multiple intracranial meningiomas are histologically benign, the prognosis is good and the same as for solitary meningiomas. 10 Nakamura et al reported the annual growth rate from 0.73 to 1.67 cm 3 per year and the tumor doubling time from 1.19 to 6.81 years.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors frequently develop in the third ventricle and supratentorial regions, such as the parietal, temporal, and occipital lobe [ 1 ]. Multiple meningiomas represent two or more meningiomas in the same patient, separated by anatomical location [ 6 ]. Three theories have been proposed to account for the etiology and pathogenesis of multiple meningiomas: multicentric dural foci; metastasis by blood-borne spread; and metastasis by the cerebrospinal fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike canine meningiomas, feline intracranial meningiomas are usually benign, fibrotic, and well encapsulated, and surgical excision is the standard treatment [ 1 , 5 ]. In the case of multiple meningiomas, which have characteristics similar to solitary meningiomas, the number of meningiomas does not have a significant effect on the survival and outcome of surgery if they have been assessed correctly and surgical resection has been performed thoroughly [ 2 , 6 ]. However, surgical resection of multiple meningiomas is associated with complications; complicated surgical plan, prolonged surgical time, intraoperative hemorrhage, and limited surgical space leading to brain parenchymal traction injury [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%